Risk Management of Occupational Health and Safety (K3) in Sanitation Health Workers at Padjonga Dg. Ngalle Hospital Takalar District in 2025 - Westy Tenriawi; Antonius Budi Trianto (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Sanitarians are health workers with the largest presentation and play an important role in providing health services, especially in controlling medical waste. In carrying out their duties Sanitarians are at risk of experiencing occupational health and safety (K3) disorders. This study aims to analyze the K3 risks of Sanitarian personnel in the sanitation room of Padjonga Dg.Ngalle Regional General Hospital, Takalar Regency in order to find appropriate risk control efforts so that Sanitarians avoid work accidents and occupational diseases. This descriptive qualitative research has been conducted on all Sanitarians in the sanitation room totaling 10 people (total sampling), risk assessment refers to the AS / NZS standard on Risk Management. To assess likelihood, exposure, and consequence, interview guidelines and job hazard analysis forms were used. It was concluded that the greatest level of danger was obtained in the act of separating medical and non-medical waste in the form of radiation risks of hazardous pipe materials, anesthetic gases, incorrect body position or ergonomic disorders, The hospital is advised to make further control efforts in accordance with the K3 control hierarchy.